2012
DOI: 10.21109/kesmas.v7i3.57
|View full text |Cite
|
Sign up to set email alerts
|

Status Gizi Ibu dan Berat Badan Lahir Bayi

Abstract: AbstrakBerat badan lahir 2.500 gram yang hingga kini merupakan standar ukuran risiko morbiditas dan mortalitas bayi merupakan faktor risiko penting yang berdampak hingga usia dewasa. Saat ini, bayi dengan berat badan lahir di bawah 3.000 gram dihubungkan dengan risiko penyakit degeneratif pada usia dewasa. Penelitian ini bertujuan mengetahui hubungan berat badan lahir dengan status gizi ibu meliputi berat badan prahamil, pertambahan berat badan selama kehamilan, dan kadar hemoglobin ibu pada trimester ketiga k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 11 publications
0
7
0
11
Order By: Relevance
“…31 Furthermore, LBW infants have serious health problems, such as cerebral palsy, mental retardation, and even cardiovascular disease, when they become adults. 32 In study by Karima, 33 pre-pregnancy weight, weight gain during pregnancy, maternal age, and birth order were factors affecting birth weight significantly, with pre-pregnancy weight as the dominant factor (OR = 6.643, CI: 2.3-18.8). Therefore, it is important to pay more attention to undernourished women who are planning a pregnancy.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…31 Furthermore, LBW infants have serious health problems, such as cerebral palsy, mental retardation, and even cardiovascular disease, when they become adults. 32 In study by Karima, 33 pre-pregnancy weight, weight gain during pregnancy, maternal age, and birth order were factors affecting birth weight significantly, with pre-pregnancy weight as the dominant factor (OR = 6.643, CI: 2.3-18.8). Therefore, it is important to pay more attention to undernourished women who are planning a pregnancy.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, it is important to pay more attention to undernourished women who are planning a pregnancy. 33 Pre-pregnancy weight and maternal weight gain in the first, second, and third trimesters have a moderate power relation and positive pattern. 34 Protein is important for fetal development because one of its roles is to form fetal cells and tissues.…”
Section: Discussionmentioning
confidence: 98%
“…Pola makan makanan pokok memiliki hubungan yang paling besar terhadap penambahan berat badan ibu hamil. Penelitian ini sejalan dengan penelitian Karima dan Achadi (2012) yang menyatakan bahwa ibu hamil dengan status gizi kurang akan berdampak pada BBLR [12]. Hal ini juga sejalan dengan penelitian Haryani dkk.…”
Section: Hubungan Antara Status Gizi Dan Pola Makan Terhadap Penambahunclassified
“…Human quality is determined from the beginning of the fetus growing [1]. The results of several studies in Indonesia found that low pre-pregnancy weight correlated with low weight gain during pregnancy [2], resulting in an increased risk of preterm birth, low birth weight (LBW) and low birth length (LBL) [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Women have lower bone mass and lose bone mass faster than men [2]. Achieving the peak of optimal bone mass formation that is maintained will be able to prevent osteoporosis in the future [2]. Various kinds of nutrients play a role in the formation of bone structure, metabolism and bone strength.…”
Section: Introductionmentioning
confidence: 99%